ANALISIS PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN FIQIH KELAS VI DI TINGKAT MADRASAH IBTIDAIYAH BAMBAN GIRIWOYO - Khoriyah, Risma Ihwanul; Mukminin, Amir (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
This research discusses the contextual approach in teaching fifth grade fiqh at Madrasah Ibtidaiyah Muhammadiyah Bamban Giriwoyo. This research aims to identify and analyze the application of a contextual approach in learning fiqh at Madrasah Ibtidaiyah Bamban Giriwoyo. The method used is a qualitative approach with case studies, which allows in-depth exploration of the phenomenon under study. Data was collected through participant observation, in-depth interviews with teachers and students, as well as documentation studies. The research results show that applying a contextual approach can improve students' understanding of fiqh material, by taking into account local social and cultural characteristics. Apart from that, this research also identified supporting factors, including available and varied learning media being the main strength, including references from books, academic journals and electronic sources. And inhibiting factors include limited facilities and inadequate infrastructure which becomes an obstacle to the learning process. It is hoped that these findings can provide practical contributions for teachers in designing more meaningful and contextual jurisprudence learning, as well as enriching the treasures of Islamic education research.